A Common-Space Scaling of the American Judiciary and Legal Profession. (9th February 2017) - Bonica, Adam; Sen, Maya
Abstract : We extend the scaling methodology previously used in Bonica (2014 ) to jointly scale the American federal judiciary and legal profession in a common space with other political actors. The end result is the first dataset of consistently measured ideological scores across all tiers of the federal judiciary and the legal profession, including 840 federal judges and 380, 307 attorneys. To illustrate these measures, we present two examples involving the U.S. Supreme Court. These data open up significant areas of scholarly inquiry.